The Effect of Academic Supervision and Teacher Professional Competence on Teacher Performance - Dewi, Rusmala; Singh, Preeti (PPSDP International Journal of Education, 2022)
The purpose of this study is to assess the impact of academic supervision and teacher professional competence on teacher performance at SMP Negeri 5 Prabumulih. The study employs quantitative tools and an associative methodology. There are 60 teachers in the population and sample. The Slovin method was employed in the sample procedure, which was proportionate random sampling. Multiple linear regression is used in the analysis tool. The study's findings revealed that simultaneous academic supervision and teacher professional competence had a substantial influence on teacher performance at SMP Negeri 5 Prabumulih. This study was just completed to assess the influence of teacher supervision and professional competency on performance, particularly at the junior high school level. This study is designed to help school administrators enhance teacher performance by strengthening academic monitoring and ensuring optimal teacher professional competence.